Corrosion behavior of W-DLC and DLC films deposited on plasma nitrided CF170 steel in H2SO4 solution. (October 2022) - Feng, Xingguo; Hu, Hanjun; Gui, Binghua; Guo, Fangjun; Wang, Keliang; Zheng, Yugang; Zhou, Hui
Abstract: In this study, the corrosion resistance of DLC and W-DLC films deposited on plasma nitrided samples was investigated. The microstructures of the samples were characterized by XRD, SEM, TEM, XPS and Raman spectroscopy. The wettability and surface energy were analyzed by optical contact angle measurement. The potentiodynamic polarization curves were obtained in 0.5 mol/L H2 SO4 solutions. The microstructure results indicated that DLC film had higher sp 3 content, denser cross-sectional structure and smaller porosity compared to W-DLC film. Corrosion tests results showed that the DLC film deposited on the plasma nitrided sample (PN + DLC) had the lowest corrosion current density and highest corrosion potential among the samples, and the corrosion current density was decreased by more than two orders of magnitude and three times compared to untreated and W-DLC film deposited on the plasma nitrided sample (PN + W-DLC), respectively. By comparing the PN + DLC and PN+(W-DLC) samples before and after immersion, it was found that both the content of the sp 3 -C was decreased and C–O/C–H was increased. Furthermore, a higher reduction of the sp 3 -C and more increase in the C–O/C–H was observed for PN+(W-DLC) sample compared to the PN + DLC sample, and the tungsten of PN+(W-DLC) had been obviously oxide. Highlights: DLC and W incorporated (W-DLC) films deposited on plasma nitrided samples were prepared. FeSO4, Fe–OOH, Fe2 O3, Cr2 (SO4 )3, Cr(OH)3 and Cr2 O3 are formed after corrosion test. The PN + DLC sample exhibits the best corrosion resistance. For both PN+(W-DLC) and PN + DLC samples, the content of sp 3 was decreased and C–O/C–H was increased.